Handling Simulation of Vehicles - Chalupa, Milan; Veverka, Josef (Manufacturing Technology Journal, 2016)
The article describes the vehicle passability testing possibilities by the help of computational simulation with the usage of computing simulation system ADAMS AVT. The simulation calculations can help to find quick answers to basic and additional questions of design change influences in the area of testing vehicle passability. The first part of the article contents description of partial computation simulation models construction which the calculations are associated with. The binding conditions of calculations are mentioned also. In the second part of the article, there are mentioned and evaluated the results of performed simulation calculations. These calculations are performed in order to find out an influence of operation conditions on the vehicle passability. Real operation condition is invasive vehicle speed into a slope in this case. Under investigation is the change of the gradient angle uphill maximum and beaten distance uphill that is the vehicle able to overcome.
Keywords: simulation; computational modeling